Spanish Science and cutbacks - Verdoy, SJ, Alfredo (Razón y fe, 2018)
The public R&D Spanish system is facing significant budget cuts in 2013 that summed up to those of 2012 and 2011. These cuts, which are well above average cuts, will seriously affect the whole R&D system while they seem to have little impact on public opinion. Without sufficient R&D investments, Spanish companies will remain insufficiently competitive and we condemn ourselves to be just a country of low value-added services and tourism, unable to create skilled and stable jobs, among other negative effects. But, unfortunately, it is not enough to invest in R&D, it is also necessary: to educate on the importance of science, to review the resource allocation processes to make them more efficient, a new framework for spin-offs and procedures so that public investments and decisions can be reviewed or audited.